2018
DOI: 10.1017/s1355617718000395
|View full text |Cite|
|
Sign up to set email alerts
|

Self-Reference Effect and Self-Reference Recollection Effect for Trait Adjectives in Amnestic Mild Cognitive Impairment

Abstract: These results indicate that while memory for trait adjective words can be improved in aMCI with deep encoding strategies (whether self-reference or semantic), self-referencing does not provide an additional benefit. (JINS, 2018, 24, 821-832).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 87 publications
(120 reference statements)
0
3
0
Order By: Relevance
“…Previous research on the SRE in dementia have focused the states of consciousness linked with memory recall rather than the effect in general. However, research in this area is still limited (Carson et al, 2018). Lalanne et al (2013) reported that prior to their work, the SRE on long-term episodic memory and autonoetic consciousness was primarily studied in young individuals, rarely in older adults, and never in AD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on the SRE in dementia have focused the states of consciousness linked with memory recall rather than the effect in general. However, research in this area is still limited (Carson et al, 2018). Lalanne et al (2013) reported that prior to their work, the SRE on long-term episodic memory and autonoetic consciousness was primarily studied in young individuals, rarely in older adults, and never in AD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Following a retention interval, the participants were given an incidental recall or recognition test. The researchers believed that "remember" and "know" responses reflect qualitatively distinct components of recognition memory (Conway and Dewhurst, 1995;Carson et al, 2018). The "remember" responses reflect episodic memory, which in turn represents self-awareness.…”
Section: Introductionmentioning
confidence: 99%
“…, 2002 ), which has led some to conceptualize self-appraisal as a primarily semantic task ( Klein, Sherman, et al. , 1996b ; Symons and Johnson, 1997 ; Carson et al. , 2018 ).…”
mentioning
confidence: 99%